Effects of inundation on water quality and invertebrates in semiarid floodplain wetlands. Issue 3 (3rd July 2022) - Tsoi, Wing (Iris); Growns, Ivor; Southwell, Mark; Mika, Sarah; Lewis, Sam; Ryder, Darren; Frazier, Paul
ABSTRACT: Floodplain wetlands play a significant role in the storage of sediment and water and support high levels of nutrient cycling driven by intermittent inundation. In regulated rivers, the frequency and duration of floodplain inundation are often reduced. Managed water inundation is used as a tool to help restore floodplains, but its outcome on wetlands requires further quantification. We examined the effects of environmental floodplain watering on water quality and 3 groups of invertebrates, including benthic and pelagic microinvertebrates and macroinvertebrates, in 2 wetlands systems on the Gwydir River system in the north of the Murray-Darling Basin. We hypothesised that a wetland inundated for longer periods would alter water quality and support a greater richness and abundance of invertebrates, thus altering their assemblage structures. Water quality and the assemblage structure of all 3 invertebrate groups in the wetlands were significantly influenced by the time since connection (TSC) to their rivers and therefore the length of inundation. However, the response of water quality and the microinvertebrate assemblages to TSC differed between the 2 wetlands. Water quality was affected by an increase in 6 variables, including total nitrogen, and a decrease in soluble reactive phosphorus. Microinvertebrate abundance was positively associated with TSC, but the abundance of macroinvertebrates was not. The relationships demonstrated between TSC and invertebrates indicate that the duration of inundation is important for ecological structure and food webs in these and other semiarid floodplain wetlands.